تصميم وتطوير موقع ويب لتسيير قرعة العمرة على مستوى الجامعة - قسومي الصديق; لعبيدي محمد ياسين (university of eloued جامعة الوادي, 2024)
تماشيا مع التطورات التكنولوجية الحديثة، قمنا بتطوير موقع ويب يُجري عمليات العمرة بأسلوب رقمي وجذاب على مستوى الخدمات الاجتماعية بجامعة الوادي. يُعد هذا التطوير خطوة نحو تحديث وتحسين الخدمات المقدمة، حيث يسعى الموقع إلى تيسير عملية التسجيل لجميع العمال والأساتذة، وذلك بهدف توفير الوقت والجهد وإضفاء الشفافية على عملية القرعة. بفضل هذا الموقع، يمكن للمستفيدين القيام بعملية التسجيل بسهولة كما يسهل لمكتب الخدمات الاجتماعية عملية معالجة الملفات. وبالتالي، يسهم هذا التطوير في تعزيز الكفاءة والفعالية في إجراءات العمرة على مستوى الجامعة In line with modern technological advancements, we have developed a website that conducts Umrah operations in a digital and attractive manner within the social services sector at El-Oued University. This development represents a step towards updating and improving the provided services, as the website aims to facilitate the registration process for all workers and professors, with the goal of saving time and effort and adding transparency to the lottery process. Thanks to this website, beneficiaries can easily complete the registration process, and it simplifies file processing for the social services office. Consequently, this development contributes to enhancing efficiency and effectiveness in Umrah procedures at the university level.
مدكرة ليسانس اعلام الي
Keywords: موقع ويب ، برنامج سطح المكتب ، قاعدة بيانات ، القرعة; lottery; database; software; Website